The Influence of Global Macroeconomic Indicators and the DJIA on Indonesia’s IDX Composite During the Iran–Israel Conflict - Grace Citra Dewi; Amir Amir; Irhamsyah Irhamsyah; Nanta Sigit (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The escalating geopolitical tensions resulting from the Iran–Israel conflict have impacted the stability of global financial markets, including the movement of the Jakarta IDX Composite in Indonesia. This study aims to analyze the influence of world gold prices, exchange rates, world oil prices, and the Dow Jones Industrial Average (DJIA) on the IDX Composite before, during, and after the Iran–Israel conflict. The study uses a descriptive quantitative approach with secondary data in the form of daily IDX Composite data and macroeconomic variables from February to July 2025. The analysis technique used is multiple linear regression with the help of EViews software and supported by classical assumption tests. The results show that world gold prices have a significant negative effect on the IDX Composite only during the conflict period, while the exchange rate has a significant negative effect before and after the conflict. World oil prices have a significant positive effect before and after the conflict, while the DJIA index has no significant effect throughout the entire study period. Simultaneously, all independent variables have a significant effect on the IDX Composite. These findings indicate that global factors and geopolitical risks play an important role in shaping the dynamics of the Indonesian capital market and are important considerations for investors and policymakers in facing global economic uncertainty.